ANALISIS TINGKAT BISING PADA MESIN MOLEN DAN PENGARUH TERHADAP PRODUKTIVITAS KERJA DI CV. XYZ - Athok Urrahman; Sajiyo Sajiyo (LPPM Universitas Bina Bangsa, 2023)
Noise is still a serious problem. Like other problems, noise can also reduce the quality of life in humans and create a threat of danger to humans. Usually the noise occurs in traffic, and industry. Noise in the workplace must always be controlled to create a safe work area for workers. Problems such as health problems, psychological disorders, and communication disorders are the main problems that need to be controlled. Therefore this study aims to control noise that exceeds the applicable regulations. After leq analysis, the results obtained are operator point 3 = 104 dBA operator point 5 = 95.6 dBA, operator point 2 = 92.4 dBA, operator point 1 = 88.4 dBA, and operator point 4 = 85.5 dBA with an average -average 93.2 dBA . Then the results of the hypothesis test showed a correlation value of -0.885 and a significant value of 0.019 <0.05, which means that there is a negative and significant relationship between noise and productivity